Analgesic Potency Of Ibuprofen, Paracetamol, And Mephenamic Acid: A Randomized Controlled Trial - Nayoan, Christin Rony; Syamsi, Nur (RSUP Dr. Kariadi, 2023)
BACKGROUND: Analgesics are a group of drugs to relieve pain. The use of analgesics is quite high, around 22.8% is used per year. Selection of analgesic drugs having adequate potency and minimal side effects is needed. Common analgesics publicly known involve paracetamol 500 mg, mefenamic acid 500 mg, and ibuprofen 400 mg. This study aims to compare the analgesic potency of paracetamol 600 mg, ibuprofen 600 mg and mefenamic acid 500 mg. METHODS: This study used a double blind randomized control trial. The study population was healthy subjects. The study sample consisted of 30 subjects with the inclusion criteria involve normal vital signs, while the exclusion criteria involve history of allergy to NSAID class drugs. This study consisted of three groups namely group 1 (K1)= paracetamol 600 mg, group 2 (K2)= mefenamic acid 500 mg, group 3 (K3)= ibuprofen 600 mg. Each subject was given medication according to the group and their pain latency (the time of onset of constant and unbearable pain) was measured every 30 minutes RESULTS: The repeated ANOVA test shows P= 0.1507 meaning that no significantly different analgesic potency was found between groups. CONCLUSION: Paracetamol 600 mg, mefenamic acid 500 mg and ibuprofen 600 mg have equal analgesic potency.